Pedagogical Mediation by Academic Librarians with ICT for the Development of Critical Thinking in Library and Information Science Students: A Systematic Review - Kayode Sunday John Dada; romoke Opeyemi Quadir (EduLine: Journal of Education and Learning Innovation, 2026)
This systematic review examines how pedagogical mediation by academic librarians using Information and Communication Technologies (ICT) contributes to the development of critical thinking among Library and Information Science (LIS) students at Ahmadu Bello University (ABU), Zaria. Employing the PRISMA 2020 framework, 81 peer-reviewed empirical studies published between 2013 and 2026 were identified, screened, and synthesised from SCOPUS, Web of Science, and supplementary databases. The review is grounded in the Technological Pedagogical Content Knowledge (TPACK) framework of Mishra and Koehler (2006). Qualitative thematic synthesis and quantitative Kruskal-Wallis nonparametric analysis were applied to compare critical thinking skill development, ICT tool effectiveness, assessment strategies, and institutional challenges across undergraduate students, postgraduate students, and academic librarians. Results reveal that problem-based learning with ICT (? = .48, p < .001) and blended learning environments (? = .41, p < .001) are the most effective pedagogical approaches for developing critical thinking, while lack of ICT pedagogical training (H = 14.67, p < .001) and role ambiguity for academic librarians (H = 13.77, p < .001) emerge as the most significant barriers. Findings indicate that integrating TPACK-aligned pedagogical training for academic librarians substantially enhances their mediation capacity and, consequently, student critical thinking outcomes in LIS education at ABU Zaria.